The Golden Age of Global Health is Over. What Follows? - Derek Yach; Aviva Ron; Dorit Nitzan (Journal of Epidemiology and Global Health)
Abstract This article examines the rise and fall of global health’s so-called golden age, from the 1990s to the early 2020s, a period marked by multilateral cooperation, historic funding increases, and major institutional innovations. It highlights the factors that have led to the decline—including funding cuts, political shifts, and emerging global crises—and argues for a reimagined framework for global health going forward. Recommendations include diversifying funding, empowering regional coalitions, adapting new governance models, and defending the principle of health equity. Without such reforms, the next era risks deepening global disparities in health outcomes.